2017
DOI: 10.1371/journal.pone.0185787
|View full text |Cite
|
Sign up to set email alerts
|

Urban retail location: Insights from percolation theory and spatial interaction modeling

Abstract: Characterising road networks has been the focus of a large body of research due to it being the main driver of activities in an urban ecosystem and the structuring factor in the dynamics of the city. One of these activities, and one with the largest economical impact in a city, is retail dynamics and its evolution. Therefore, the mathematical modeling of the location of retail activities and of the emergence of clustering in retail centers has as well generated a large number of works. Despite these two interw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
(86 reference statements)
0
31
0
Order By: Relevance
“…The fundamental idea is to use the individual movement data as a proxy to reveal the structure and organisation of the city. As one of the most fundamental measures, network centrality has been used for detecting hierarchical spatial organisation (Piovani et al, 2017) and functional centres (Li and Phelps, 2018). A number of empirical studies have found that functional network centrality can effectively capture location advantage in a city and reflect intra-urban variation of land use and transport intensity and hierarchy (Roth et al, 2011, Wang et al, 2014.…”
Section: Tod and Centrality Of Movement Networkmentioning
confidence: 99%
“…The fundamental idea is to use the individual movement data as a proxy to reveal the structure and organisation of the city. As one of the most fundamental measures, network centrality has been used for detecting hierarchical spatial organisation (Piovani et al, 2017) and functional centres (Li and Phelps, 2018). A number of empirical studies have found that functional network centrality can effectively capture location advantage in a city and reflect intra-urban variation of land use and transport intensity and hierarchy (Roth et al, 2011, Wang et al, 2014.…”
Section: Tod and Centrality Of Movement Networkmentioning
confidence: 99%
“…4. Road network characterization becomes the main driver of activities in urban ecosystems and structuring factors in urban dynamics towards development distribution of gravity-based retail locations, namely road network location and cluster size depending on the threshold and scale of exponents (Piovani et al, 2017). Likewise, Ji et al (2013) that the optimization model of the location of regional express distribution centers is based on the reality of road networks by minimizing distance.…”
Section: Resultsmentioning
confidence: 99%
“…The gravity model of flow was proposed by W. Alonso [28] for modelling spatial flow phenomena between regions. It has been extensively used in the literature for modelling international air travel [29], traffic flow in highways [30], retailing [31,32] and telecommunications across cities [33], among others.…”
Section: Related Workmentioning
confidence: 99%
“…The gravity model of flow has been extensively used to model human mobility in different contexts [28,29,33], and in particular for retailing [31,32]. It considers the flow between two nodes (i, j) as directly proportional to some powers of their populations, and inversely proportional to some power of the distance between them:…”
Section: A Gravity Mobility Model For Mall Visitsmentioning
confidence: 99%